Sex differences in the gait kinematics of patients with Down syndrome: A preliminary report - Matteo Zago; Claudia Condoluci; Massimiliano Pau; Manuela Galli (Medical Journals Sweden, 2018)
Objective: Sex-specific medicine requires understanding of the specific therapeutic needs and patho-physiology of men and women. In these terms, we investigated sex-related differences in the gait kinematics of patients with Down syndrome. Design: Retrospective observational cohort study. Subjects: A sample of 230 patients (103 females) aged 7-50 years underwent a standard gait-analysis test from 2000 to 2015. Methods: Spatiotemporal gait parameters and synthetic indexes were computed as Gait Profile Score (GPS) and pelvis/lower limbs as Gait Variable Scores. Results: Although speed, normalized step width, %stance and %swing were similar, in female patients step length was shorter and GPS was higher than in male patients, with no significant effect of age, speed and body mass index. Sex-specific features were found at the pelvis, hip and knee level (sagittal plane), and at the ankle level (transverse plane). Conclusion: Overall, in people with Down syndrome, the gait function of females tends to be more impaired than in males, with the exception of foot progression. Therapists should consider these differences when evaluating the severity of gait impairment and designing rehabilitation strategies.